Knowledge management with a competitiveness focus in Family Tourism Business (FTB) from Guanajuato, Mexico - González Macías, Carlos Jesús (2019)
Knowledge management in Family Tourism Businesses (FTB) represents a critical process towards competitiveness. This research aims to know how knowledge management practices are related to the levels of competitiveness in the FTB of the city of Guanajuato, Mexico. Considering the Intelligent Organization Model, a quantitative approach was conducted through the application of questionnaires (104) to owners, family members, managers and employees of 18 FTB. This model is contrasted with the evidence of the results, concluding that there is a framework to determine the degree of knowledge management to lead these companies towards competitiveness, where they can create, develop, disseminate and optimize all activities within, in order to generate value by encouraging learning and the sharing of knowledge and experience as competitive advantages.